2019
DOI: 10.1177/0144598719886188
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of elements in coal seams 41 and 42 of Heshan Coalfield, South China

Abstract: Coal seams 41 and 42 of the Heshan Coalfield belong to superhigh-organic-sulfur coals. In order to study the geochemical characteristics of the coals, 15 coal samples and 6 rock samples were collected from both coal seams and the roof/floor rocks. The samples were investigated by using conventional microscopy, inductively coupled plasma mass spectroscopy, X-ray diffraction, X-ray fluorescence, and scanning electron microscopy with an energy-dispersive X-ray spectroscopy. The results show that minerals in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Such affinity of Si is widely reported from various coals around the World (i.e. Beaton et al, 1991;Crowley et al, 1997;Warwick et al, 1997;Spears, Zheng, 1999;Liu et al, 2001;Zhao et al, 2017Zhao et al, , 2020Finkelman et al, 2019;Životić et al, 2019). Furthermore, Querol et al (1997aQuerol et al ( , b, 2001a, Ward et al (1999), Karayigit et al (2000aKarayigit et al ( , 2020 and Alastuey et al (2001) accept a priori the exclusive relationship of Si with the clay minerals and use the correlation of the element with the alumino-silicate part of the ash to determine its mode of occurrence.…”
Section: Resultsmentioning
confidence: 95%
“…Such affinity of Si is widely reported from various coals around the World (i.e. Beaton et al, 1991;Crowley et al, 1997;Warwick et al, 1997;Spears, Zheng, 1999;Liu et al, 2001;Zhao et al, 2017Zhao et al, , 2020Finkelman et al, 2019;Životić et al, 2019). Furthermore, Querol et al (1997aQuerol et al ( , b, 2001a, Ward et al (1999), Karayigit et al (2000aKarayigit et al ( , 2020 and Alastuey et al (2001) accept a priori the exclusive relationship of Si with the clay minerals and use the correlation of the element with the alumino-silicate part of the ash to determine its mode of occurrence.…”
Section: Resultsmentioning
confidence: 95%
“…This is mainly due to the unusual coal-forming environment of the GH sample (Dai et al., 2008), which has the highest organic sulfur content among all samples and experienced strong biodegradation in the later coalification. The result is the conversion of high carbon number alkanes to low carbon numbers, leading to an increase in the proportion of vibration peaks at 1300–1450 cm −1 (Zhao et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Coal with an organic sulfur content of 4% to 11% is referred to as superhigh-organic-sulfur (SHOS) coals (Chou, 1997). The SHOS coals and their very high organic sulfur contents, are not common and have attracted the attention of researchers (Dai et al., 2008, 2017, 2018; Li and Tang, 2014; Li et al., 2015; Medunić et al., 2020; Smith and Batts, 1974; Torres-Ordonez et al., 1990; White et al., 1990; Zhao et al., 2014, 2020). In some special cases the sulfur content in coal is high and the organic sulfur content exceeds 50% of total sulfur (Dai et al., 2008, 2017, 2018; Li and Tang, 2013, 2014; Li et al., 2015; Medunić et al., 2016b; Sinninghe Damsté et al., 1999; Smith and Batts, 1974; Torres-Ordonez et al., 1990; White et al., 1990; Zhao et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed organic/inorganic affinity (Beaton et al, 1991;Querol et al, 1997a;Sutcu, Karayiğit, 2015) or predominant inorganic affinity of Fe (Gluskoter et al, 1977;Querol et al, 1997bQuerol et al, , 2001aLiu et al, 2001;Zhao et al, 2017Zhao et al, , 2020Životić et al, 2019;Karayiğit et al, 2020) are much more readily reported. The research of Querol et al (2001b) on the mode of occurrence of selected elements in coal indicates organic affinity of only ~5-12% of iron.…”
Section: Resultsmentioning
confidence: 99%